2022
DOI: 10.1021/acs.jpcc.2c07247
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Two-Dimensional Allotrope of Silicon Grown on Al(111): A Case Study of the Interface Effect

Abstract: Based on density functional calculations, a novel planar allotrope of silicon on Al( 111) is rationally designed by using the lowest energy principle, which is also predicted to be stable above room temperature to suggest the possibility for its fabrication. The corresponding free-standing sheet would be buckled though the structural characteristics still remain, whose stability has also been evaluated in detail. It has been found to have strong anisotropic properties to be as hard as silicene in a specific di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The t - and h -PBAs are calculated to have −1.00 and −1.17 eV/atom formation energies, indicating the possibilities of their fabrications. In addition, considering the fact that (111)-oriented metallic surfaces of Au, ,,, Pt, , Al ,, metals, etc. are usually used as substrates for 2D material fabrications in experiments, we have performed a tentative study by putting PBAs on the Al(111) surface.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The t - and h -PBAs are calculated to have −1.00 and −1.17 eV/atom formation energies, indicating the possibilities of their fabrications. In addition, considering the fact that (111)-oriented metallic surfaces of Au, ,,, Pt, , Al ,, metals, etc. are usually used as substrates for 2D material fabrications in experiments, we have performed a tentative study by putting PBAs on the Al(111) surface.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 1a, the pyracyclene molecule has a planar structure consisting of two C 6 hexagons and two C 5 pentagons, 32,33 having similar geometrical configuration characteristics as to the structural motif of a recently proposed silicene allotrope grown on an Al(111) surface. 31 In Figure 1a, the nonequivalent C atoms are marked to facilitate discussion. The 1,2-, 2,3-, and 2,4-bonds are calculated to be 1.49, 1.39, and 1.41 Å, respectively.…”
Section: Geometrical Configurationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the complex potential energy surface, the Group-IV elements can form various allotropes with different structural and electronic properties, which provides promising platforms for constructing multifunctional microelectronic devices. Hence, the searching for stable Group-IV allotropes has attracted considerable attention from both theoretical and experimental researchers. However, these studies mainly focus on carbon (C) and silicon (Si), and the studies about germanium (Ge) allotropes are relatively few. The most prominent Ge allotrope is the diamond-cubic Ge, denoted as dc-Ge, which has higher electron and hole mobilities, and smaller indirect band gap with respect to that of dc-Si .…”
Section: Introductionmentioning
confidence: 99%
“…In very recent years, new two-dimensional silicon allotropes were discovered theoretically. For example, Ding et al [25] designed a novel planar allotrope of silicon on Al(111) and found that the hydrogenated sheet is also quite stable than freestanding one. More interestingly, Sang et al [26] discovered a two-dimensional allotrope with hybrid honeycomb-kagome (hhk) lattice, which is a semiconductor instead of quasi-zero Dirac-cone like graphene and graphene-like silicene.…”
Section: Introductionmentioning
confidence: 99%